Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization - Tawade, Bhausaheb V.; Salunke, Jagadish K.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2014)
A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50: 50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co) polyesters exhibited inherent viscosities in the range 0.70-1.21 dL g(-1) and number-average molecular weights in the range 16,000-48,200 (GPC, polystyrene standard). Polyesters were soluble in common organic solvents such as chloroform and dichloromethane and could be cast into films from chloroform solution. Polyesters exhibited T-10 values in the range 430-455 degrees C and Tg values were in the range 29-202 degrees C. Dynamic mechanical storage modulus and maximum on transition of tan delta curve decreased with increased content of HPPDP in copolyesters. Importantly, the large difference between Tg and T-10 values offers the possibility to process these polyesters in the melt.
Keywords: Aromatic polyesters; Cashew nut shell liquid; pentadecyl; Polycondensation; processability; Thermal properties